2009
DOI: 10.2478/v10101-009-0002-1
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of muscle strength in elite athletes

Abstract: Asymmetry of muscle strength in elite athletes Study aim: To determine muscle strength variables in elite judoists and wrestlers since thigh muscle strength and bilaterally balanced flexor-to-extensor ratio minimise injury risk and are desirable for achieving sport successes. Material and methods: Judoists, wrestlers and untrained subjects, 10 each, were subjected to isokinetic strength measurements of relative peak torques of knee flexor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…In the present study that ratio was higher in young and in adolescent male football players (1.18 and 1.11, respectively) than in untrained subjects (0.84) which was suggestive of a flexors/extensors misbalance in football players, which was also noticed in another research in female football players (1.19; [11]). Such a misbalance, combined with sport-specific asymmetric work, may bring about postural disorders [3] in addition to other implications in performance induced by misbalances between agonist and antagonist muscles [2].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study that ratio was higher in young and in adolescent male football players (1.18 and 1.11, respectively) than in untrained subjects (0.84) which was suggestive of a flexors/extensors misbalance in football players, which was also noticed in another research in female football players (1.19; [11]). Such a misbalance, combined with sport-specific asymmetric work, may bring about postural disorders [3] in addition to other implications in performance induced by misbalances between agonist and antagonist muscles [2].…”
Section: Discussionmentioning
confidence: 99%
“…Research papers have shown that ipsilateral ratios are valid tools to assess the effectiveness of rehabilitation protocols (Brown et al, 2000; Dvir et al, 2004; Impellizzeri et al, 2007; Drid et al, 2009a). Many papers report that bilateral differences are an important predictor of injury occurrence (Dauty et al, 2003; Yeung et al, 2009; Fousekis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In kayaking, both upper limbs are used symmetrically in the movement of drawing the paddle while is a seated position; in canoeing, however, a canoeist draws the paddle on one side while kneeling on one leg, which -as is suspected -may imply the presence of strength asymmetry in different muscle groups. Drid et al [5] indicated that kayakers' muscle strength is distributed symmetrically, but similar results were not reported with regards to canoeists. The attempts to compare the strength symmetry in both disciplines in the same tests were not conducted.…”
Section: Introductionmentioning
confidence: 90%